Obtención de una mezcla de concreto con residuos plásticos de equipos electrónicos para la fabricación de elementos no estructurales (2017)
The accelerated increase in population growth rate in the world and the current lifestyle based on consumerism have considerably increased the amount of waste generated by human activity. Specifically, electronic waste causes significant damage to the environment as a result of its difficult degradation process. This research aims to establish the feasibility of implementing electronic waste of plastic type (E-Waste) in the construction of non-structural concrete used in the construction by performing tests to know the compressive strength of mixtures with 40%, 50% And 60% of plastic aggregate replaced on the basis of the amount of coarse aggregate obtained for a 21 MPa blend design of f'c made with conventional materials traditionally implemented in the manufacture of concrete, all this taking into account the standards of durability and strength Required.